Somatic mutations and deletions of the E-cadherin gene predict poor survival of patients with gastric cancer. - Corso, G (2013)
Purpose The prognosis of gastric cancer (GC) is poor, and the molecular pathogenesis players are vastly unknown. Surgery remains the primary option in GC treatment. The aim of this study was to investigate the impact of somatic CDH1 alterations in prognosis and survival of patients with GC. Patients and Methods A series of patients with sporadic and familial GC (diffuse and intestinal; n _ 246) were analyzed for somatic CDH1 mutations, promoter hypermethylation, and loss of heterozygosity (LOH) by polymerase chain reaction sequencing. E-cadherin protein expression was determined by immunohistochemistry. Associations between molecular, clinicopathologic, and survival data were analyzed. Results CDH1 somatic alterations were found in approximately 30% of all patients with GC. Both histologic types of sporadic GC displayed LOH in 7.5%, mutations in 1.7%, and hypermethylation in 18.4% of patients. Primary tumors from hereditary diffuse GC, lacking germline CDH1 alterations, showed exclusively CDH1 promoter hypermethylation in 50% of patients. Familial intestinal GC (FIGC) tumors showed LOH in 9.4% and hypermethylation in 17.0%. CDH1 alterations did not associate with a particular pattern of E-cadherin expression. Importantly, the worst patient survival rate among all GCs analyzed was seen in patients with tumors carrying CDH1 structural alterations, preferentially those belonging to FIGC families. Conclusion CDH1 somatic alterations exist in all clinical settings and histotypes of GC and associate with different survival rates. Their screening at GC diagnosis may predict patient prognosis and is likely to improve management of patients with this disease.